An Aspect in Selection of Species for Afforestation with special Reference to Soil & Water Conservation - Roy, A B (Journal of Soil and Water Conservation, 2022)
The rain—a paramount resource conservation, control of its flow, its best utilization have been talked of so many times and their repetition, though not unnecessary, will only sound as an echo of the previous talks. It is by now an admitted fact that any type of vegetative cover-controls soil and water loss, more or less effectively, depending upon the character of the vegetative cover. This paper will, however, present än aspect of the choice of species for afforestation works in a soil and water conservation programme.